2010
DOI: 10.1038/sj.bjc.6605548
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fracture risk in women with breast cancer using current vs emerging guidelines

Abstract: BACKGROUND: Breast cancer (BC) therapies can have negative effects on bone. Current guidelines recommend antiresorptive therapy based on bone mineral density (BMD), and emerging guidelines include both clinical risk factors and BMD to assess the overall fracture risk. A retrospective, case -controlled study based on current and emerging guidelines was conducted in women with newly diagnosed BC to identify those who were at increased fracture risk based on current and emerging guidelines. METHODS: Baseline char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Consequently, total T-and Z-Scores after chemotherapy were also significantly (p<0.001) lower than those before chemotherapy, confirming that bone loss was directly related to treatment with adjuvant chemotherapy. In line with this, many studies reported that adjuvant chemotherapy may cause a rapid bone loss, increasing the risk of osteoporosis for pre-and postmenopausal women with BC later in life [1][2][3][4][5][6][7][24][25][26][27]. It has been shown that bone loss with aging occurs because hypogonadism may progress to primary osteoporosis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Consequently, total T-and Z-Scores after chemotherapy were also significantly (p<0.001) lower than those before chemotherapy, confirming that bone loss was directly related to treatment with adjuvant chemotherapy. In line with this, many studies reported that adjuvant chemotherapy may cause a rapid bone loss, increasing the risk of osteoporosis for pre-and postmenopausal women with BC later in life [1][2][3][4][5][6][7][24][25][26][27]. It has been shown that bone loss with aging occurs because hypogonadism may progress to primary osteoporosis.…”
Section: Discussionmentioning
confidence: 95%
“…BC accounts for 37.6% of all reported tumors in Egyptian females, with an age-adjusted incidence rate of 49.6 per 100,000 females [2]. BC, prostate cancer, and multiple myeloma have particularly shown strong doi: 10.7243/2057-1631-1-1 association with skeletal metastases and related bone loss, resulting in fracture, hypercalcemia, pain, and declines in mobility and performance status [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,70 The case study discussed herein represents one potential illustrative example. The patient concerned would not have been eligible for zoledronic acid treatment based on her scans at 12 months because the t score was more than −2 and there was an absence of other risk factors, eg, family history.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference in fracture rate was observed between letrozole (5.7%) and the tamoxifen arm (4.0%; p < 0.001) at 25.8 months of median [46,58]. Evaluating both BMD and clinical risk factors may allow for the most effective identification of breast cancer patients with increased risk of fracture and the appropriate use of preventative therapies [59].…”
Section: Letrozolementioning
confidence: 99%